Critical illness myopathy is frequent: accompanying neuropathy protracts ICU discharge. Issue 3 (27th August 2010) - Koch, Susanne; Spuler, Simone; Deja, Maria; Bierbrauer, Jeffrey; Dimroth, Anna; Behse, Friedrich; Spies, Claudia D; Wernecke, Klaus-D; Weber-Carstens, Steffen
Abstract : Objectives: Neuromuscular dysfunction in critically ill patients is attributed to either critical illness myopathy (CIM) or critical illness polyneuropathy (CIP) or a combination of both. However, it is unknown whether differential diagnosis has an impact on prognosis. This study investigates whether there is an association between the early differentiation of CIM versus CIP and clinical prognosis. Methods: The authors included mechanically ventilated patients who featured a Simplified Acute Physiology Score II (SAPS-II) ≥20 on three consecutive days within the first week after intensive care unit (ICU) admission. Fifty-three critically ill patients were enrolled and examined by conventional nerve-conduction studies and direct muscle stimulation (184 examinations in total). The first examination was conducted within the first week after admission to the ICU. Results: In this cohort of critically ill patients, CIM was more frequent (68%) than CIP (38%). Electrophysiological signs of CIM preceded electrophysiological signs of CIP (median at day 7 in CIM patients vs day 10 in CIP patients, p<0.001). Most patients with CIP featured concomitant CIM. At discharge from ICU, 25% of patients with isolated CIM showed electrophysiological signs of recovery and significantly lower degrees of weakness. Recovery could not be observed in patients with combined CIM/CIP, even though the ICU length of stay was significantly longer (mean 35 days in CIM/CIP vs mean 19 days in CIM, p<0.001). Conclusion: Prognoses of patients differ depending on electrophysiological findings during early critical illness: early electrophysiological differentiation of ICU acquired neuromuscular disorder enhances the evaluation of clinical prognosis during critical illness.